2008
DOI: 10.1525/cond.2008.110.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Buff-Breasted Sandpiper Density and Numbers During Migratory Stopover in the Rainwater Basin, Nebraska

Abstract: Abstract. The Buff-breasted Sandpiper (Tryngites subruficollis) is a shorebird of conservation concern whose migration patterns and population size are poorly known. We conducted surveys in the Eastern Rainwater Basin, Nebraska, in 2004 and 2005 using distance sampling. This survey produced density estimates of 0.09 birds per ha in 2004 and 0.04 birds per ha in 2005. Because the study area was explicitly defined by soil characteristics, we were able to extrapolate from density estimates to produce predictions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Croplands are not a habitat type located with some systematic bias away from roads (Harris andHaskell 2007, Niemuth et al 2007). Thus, as Jorgensen et al (2008) concluded for sampling buff-breasted sandpipers Tryngites subruficollis along roads in the eastern Rainwater Basin, Nebraska, we believe a roadside-based survey in the lower Mississippi Flyway samples representative snipe habitats available there. Logistically, using a roadside-based survey is effective because we could conduct a large number of surveys over a short period of time, we could detect a large number of snipe, and we could survey privately-owned lands from public roads.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Croplands are not a habitat type located with some systematic bias away from roads (Harris andHaskell 2007, Niemuth et al 2007). Thus, as Jorgensen et al (2008) concluded for sampling buff-breasted sandpipers Tryngites subruficollis along roads in the eastern Rainwater Basin, Nebraska, we believe a roadside-based survey in the lower Mississippi Flyway samples representative snipe habitats available there. Logistically, using a roadside-based survey is effective because we could conduct a large number of surveys over a short period of time, we could detect a large number of snipe, and we could survey privately-owned lands from public roads.…”
Section: Resultsmentioning
confidence: 57%
“…soybean stubble or actively growing winter wheat). Jorgensen et al (2008) found that conducting roadside surveys when fields were bare or before crops began to grow allowed for increased detection distances and subsequently enabled observers to detect birds at longer distances from the road. Vegetation height can have direct impacts on detection if it is tall enough to obstruct the view of snipe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, birds that breed in the arctic need to be protected from the direct and indirect effects of oil and gas development, which is reducing habitat quality and potentially increasing predation rates (Liebezeit et al 2009). Major stopover sites in the central U.S. need to be managed carefully to prevent further losses of suitable habitat and reduce chemical contamination (Jorgensen et al 2008;Strum et al 2010). Last, habitat degradation in winter sites across Brazil, Argentina, and Uruguay must be managed to limit possible habitat loss and population fragmentation (Almeida 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Birds have a broad longitudinal distribution during the breeding and nonbreeding season, but concentrate along the Central Flyway during spring and fall migration in places like the Rainwater Basin of southcentral Nebraska and coastal areas of Texas and Louisiana (Lanctot and Laredo 1994;Jorgensen et al 2008;Norling et al 2012). Like other shorebirds, this historically abundant species underwent substantial population declines in the past 150 years.…”
Section: Introductionmentioning
confidence: 99%